2009
DOI: 10.1039/b902174d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SERRS immunoassay for the detection of human PSA

Abstract: We report the first use of a commonly used ELISA colorimetric substrate as a SERRS marker and show how it can be used for the detection of pg ml(-1) levels of human prostate specific antigen (PSA) in clinical samples. The technique is amenable over a wide range of concentrations and lends itself to future multiplexing analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…[76] SERS can be used to enhance native Raman signals, by close proximity to roughened metal surfaces. However, perhaps the more promising application is to probe for specific interactions, for example by detection of specific antigens [37] or enzyme activity [18,77]. Kneipp et al[78] demonstrated the use of SERS to enhance Raman signals in single cells, therefore decreasing the acquisition time for a single map significantly.…”
Section: An Alternative Technique -Surface Enhanced Raman Spectroscopmentioning
confidence: 99%
See 2 more Smart Citations
“…[76] SERS can be used to enhance native Raman signals, by close proximity to roughened metal surfaces. However, perhaps the more promising application is to probe for specific interactions, for example by detection of specific antigens [37] or enzyme activity [18,77]. Kneipp et al[78] demonstrated the use of SERS to enhance Raman signals in single cells, therefore decreasing the acquisition time for a single map significantly.…”
Section: An Alternative Technique -Surface Enhanced Raman Spectroscopmentioning
confidence: 99%
“…In particular, the technique of surface enhanced Raman spectroscopy (SERS) has been used extensively in assay development in other biomedical research areas for many applications, including ELISA type immunoassays. [37] It has many benefits over standard fluorescence based assays, including lack of photobleaching, multiplexing ability [38] and often increased sensitivity. SERS has also been applied to in vitro cellular assays, to analyse, for example, enzyme activity.…”
Section: Current High Throughput Screening Techniques: Could Vibratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Some types of immunoassay for PSA have been reported, such as fluorescence microscopy, surface plasmon resonance technology, lateral flow immunoassay, enzyme-linked immunosorbent assay (ELISA), radioimmunoassay, immunochromatographic assay system, and SERS based on immunoassays. [15][16][17]26,[37][38][39][40][41][42][43][44] In this study, we applied a sandwich type SERS immunoassay for the detection of PSA with high sensitivity. It shows the possible application of SERS immunoassay with monoclonal antibodies that is sensitive enough for analysis of PSA in human blood samples or cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…28 Especially, SERS immunoassays based on antigen-antibody binding have been reported for biomarkers for early cancer diagnosis. [12][13][14][15][16][17][18][21][22][23][24]26,30 For successful application of SERS immunoassays for biological sensors, people usually used novel metal nanoparticles modified to integrate bioselective species (e.g., antibodies) with molecular labels for the generation of intense, biolyte-selective SERS responses in immunoassays and other bioanalytical applications.…”
Section: Introductionmentioning
confidence: 99%